The Effect Of Papaya Latex For Worms Against Worm Feed Intake And Body Weight Male Kacang Goat’s - leksi umbu ratu amah (Jurnal Sains Peternakan, 2015)
ABSTRACTThis study aims to determine the effect of papaya latex use as an anthelmintic to feed intake and weight gain of male kacang goat. Materials used male goat kacang as much as 9 male kacang goat with an average body weight of 20 kg to 35 kg. The goats were divided into 3 treatment Po : provision of drinking without papaya latex (control, P1 : provision of drinking as much as 1.2 grams / BB in half a liter of water, and P2 : provision of drinking as much as 2.4 grams / BB in 1 liter water . Food rations consisting Gliricidia sepium, Leucaena leucocephala, and Schleichera oleosa. The variables measured were feed intake and body weight gain. The data obtained were analyzed by randomized block design. The analysis showed that the effect of papaya latex in drinking water increases feed intake and body weight gain. The result showed the effect papaya latex up 2.4 gram have the  best result for feed intake and body weight gain male kacang goat’s.Keywords : male kacang goat, papaya latex, feed consumption, body weight gain.